Frizzled-7 as a Potential Therapeutic Target in Colorectal Cancer - Ueno, Koji (Neoplasia Press Inc., 2008)
We investigated whether one of the Wnt receptors, frizzled-7 (FZD7), functions in the canonical Wnt signaling pathway of colorectal cancer (CRC) cells harboring an APC or CTNNB1 mutation and may be a potential therapeutic target for sporadic CRCs. The expression level of FZD gene family members in colon cancer cells and primary CRC tissues were determined by real-time PCR. Activation of the Wnt signaling pathway was evaluated by TOPflash assay. The expression level of Wnt target genes was determined by real-time polymerase chain reaction and/or Western blot analysis. Cell growth and cell invasion were assessed by MTS and matrigel assays, respectively. Among 10 FZD gene family members, FZD7 mRNA was predominantly expressed in six colon cancer cell lines with APC or CTNNB1 mutation. These six cell lines were transfected with FZD7 cDNA together with a TOPflash reporter plasmid, resulting in a 1.5- to 24.3-fold increase of Tcf transcriptional activity. The mRNA expression levels of seven known Wnt target genes were also increased by 1.5- to 3.4-fold after transfection of FZD7 cDNA into HCT-116 cells. The six cell lines were then cotransfected with FZD7-siRNA and a TOPflash reporter plasmid, which reduced Tcf transcriptional activity to 20% to 80%. FZD7-siRNA was shown to significantly decrease cell viability and in vitro invasion activity after transfection into HCT-116 cells. Our present data demonstrated that FZD7 activates the canonical Wnt pathway in colon cancer cells despite the presence of APC or CTNNB1 mutation and that FZD7-siRNA may be used as a therapeutic reagent for CRCs.